2010
DOI: 10.1002/aoc.1627
|View full text |Cite
|
Sign up to set email alerts
|

Indazaboles—synthesis and molecular structure

Abstract: The reaction of 1-trimethylsilyl-indazole with boranes affords indazaboles accompanied by elimination of trimethysilane. Thus, the two isomers of parent indazabole are formed in a 1 : 1 ratio using borane in THF (BH 3 /THF), characterized by NMR spectroscopy in solution ( 1 H, 11 B and 13 C NMR). In contrast, the analogous reaction with 1,2-bis(tetramethylene)diborane(6) proceeds to give a single isomer of the B-alkylated indazabole via symmetric ring cleavage of the diborane(6), as shown by NMR in solution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…Importantly, this also shows that hydride-triel bond may have significant role in molecular binding and in determining molecular structure. For example, most recently we have shown [31] that the SiAHÁ Á ÁB contacts in some 1-silacyclohex-2-enes are clearly stabilizing and strong with interaction energies of the order of 4-5 kcal/mol-the result in a full agreement with earlier studies by Wrackmeyer et al [51] based on NMR spectroscopic data. Moreover, these energies can even be enhanced to 13-14 kcal/mol if 9-borabicyclo[3.3.1]nonane group is substituted by the ABH 2 one [31] (see Fig.…”
Section: Influence Of R Substituentssupporting
confidence: 91%
“…Importantly, this also shows that hydride-triel bond may have significant role in molecular binding and in determining molecular structure. For example, most recently we have shown [31] that the SiAHÁ Á ÁB contacts in some 1-silacyclohex-2-enes are clearly stabilizing and strong with interaction energies of the order of 4-5 kcal/mol-the result in a full agreement with earlier studies by Wrackmeyer et al [51] based on NMR spectroscopic data. Moreover, these energies can even be enhanced to 13-14 kcal/mol if 9-borabicyclo[3.3.1]nonane group is substituted by the ABH 2 one [31] (see Fig.…”
Section: Influence Of R Substituentssupporting
confidence: 91%
“…Numerous studies have demonstrated that the intramolecular Si-H···B bridge can maintain the conformation of compounds simultaneously containing silicon and boron atoms. [37][38][39][40][41][42] In the present paper, we study the triel bond between ZX 3 (Z = B and Al; X = H and Me) and THMe 3 (T = Si, Ge and Sn). The T-H bond in THMe 3 acts as the Lewis base in the triel bond; thus this interaction is named triel-hydride triel bond, coining the name of halogenhydride halogen bond, [43] chalcogen-hydride chalcogen bond, [44] pnicogen-hydride pnicogen bond, [45] tetrelhydride tetrel bond [46] and lithium-hydride lithium bond.…”
Section: Introductionmentioning
confidence: 99%